Pelatihan dan Pembinaan Atlet Kurash Menuju PORDA Sulawesi Selatan: Strategi Peningkatan Prestasi Daerah - Irvan, Irvan; Iskandar, Iskandar; Sufitriyono, Sufitriyono; Syafruddin, Muhammad Akbar; Sutriawan, Agus (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This community service aims to provide intensive training and coaching to 85 Kurash athletes from various regions in South Sulawesi in preparation for the Regional Sports Week (PORDA). Kurash, as a relatively new martial arts sport in Indonesia, requires a systematic and targeted coaching strategy in order to be able to compete at the regional and national levels. This activity is carried out through a structured training approach that includes mastery of basic techniques, development of match strategies, improvement of physical fitness, and strengthening of mental competition. The implementation method includes direct training, match simulations, performance evaluations, and mentoring by certified trainers. The results of the activity showed a significant increase in the technical, tactical, and physical readiness aspects of the athletes. In addition, this program also succeeded in building motivation, discipline, and fighting spirit of athletes in facing competitions. It is hoped that this program can become a model of sustainable coaching that can produce high-achieving Kurash athletes and strengthen the existence of Kurash in South Sulawesi.